Ex Vivo Human Adipose Tissue Derived Mesenchymal Stromal Cells (ASC) Are a Heterogeneous Population That Demonstrate Rapid Culture-Induced Changes - Brooks, Anna E. S.; Iminitoff, Megan; Williams, Eloise; Damani, Tanvi; Jackson-Patel, Victoria; Fan, Vicky; James, Joanna; Dunbar, P. Rod; Feisst, Vaughan; Sheppard, Hilary M. (Frontiers in Pharmacology, 2020)
Human adipose-derived mesenchymal stromal cells (ASC) are showing clinical promise for the treatment of a range of inflammatory and degenerative conditions. These lipoaspirate-derived cells are part of the abundant and accessible source of heterogeneous stromal vascular fraction (SVF). They are typically isolated and expanded from the SVF via adherent cell culture for at least 2 weeks and as such represent a relatively undefined population of cells. We isolated ex vivo ASC directly from lipoaspirate using a cocktail of antibodies combined with immunomagnetic bead sorting. This method allowed for the rapid enrichment of a defined and untouched ex vivo ASC population (referred to as MACS-derived ASC) that were then compared to culture-derived ASC. This comparison found that MACS-derived ASC contain a greater proportion of cells with activity in in vitro differentiation assays. There were also significant differences in the secretion levels of some key paracrine molecules. Moreover, when the MACS-derived ASC were subjected to adherent tissue culture, rapid changes in gene expression were observed. This indicates that culturing cells may alter the clinical utility of these cells. Although MACS-derived ASC are more defined compared to culture-derived ASC, further investigations using a comprehensive multicolor flow cytometry panel revealed that this cell population is more heterogeneous than previously appreciated. Additional studies are therefore required to more precisely delineate phenotypically distinct ASC subsets with the most therapeutic potential. This research highlights the disparity between ex vivo MACS-derived and culture-derived ASC and the need for further characterization.